2010
DOI: 10.1155/2010/170702
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Occult Celiac Disease among Patients with Functional Dyspepsia: A Study from the Western Region of Iran

Abstract: Objective. The prevalence of Celiac Disease (CD) is high in Iran, and evaluation of CD is not part of the routine screening procedure for dyspeptic patients; therefore, cases of occult CD may be missed. This study aimed to investigate the prevalence of occult CD among dyspeptic patients who presented at a gastroenterology clinic in the Western region of Iran. Methods. In this descriptive, cross-sectional prospective study, patients who had a history of at least 12 weeks of upper abdominal discomfort were eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…An antibody role against the autonomic nervous system is being suggested as a cause of functional "dysmotility" type dyspepsia-heartburn in which no organic cause can be identified. 17,18 One of this patient's primary presenting complaints was acute heartburn that was not being relieved by esomeprazole. Furthermore, the first indication of accidental gluten contamination in this patient is a return of the urticarial eczema and heartburn.…”
Section: Discussionmentioning
confidence: 99%
“…An antibody role against the autonomic nervous system is being suggested as a cause of functional "dysmotility" type dyspepsia-heartburn in which no organic cause can be identified. 17,18 One of this patient's primary presenting complaints was acute heartburn that was not being relieved by esomeprazole. Furthermore, the first indication of accidental gluten contamination in this patient is a return of the urticarial eczema and heartburn.…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that the prevalence of occult CD in patients with dyspepsia is higher than that of the general population in Egypt (Abu-Zekry et al, 2008). Another study from eastern country was conducted on 225 dyspeptic Iranian patients, revealing that about 6% of the selected patients with functional dyspepsia had occult celiac disease (Keshavarz et al, 2010). Also, Nakazawa et al (2014) found that seven of the eleven patients with anti-tTG exhibited villous atrophy and partial infiltration of intraepithelial lymphocyte.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with the general population, it was observed that CD had a greater prevalence in dyspeptic patients and that 30 to 40% of CD patients have dyspeptic symptoms. These findings suggested that it would be useful to carry out, in subjects undergoing esophago-gastro-duodenoscopy (EGD), biopsies of the descending duodenum independently of the endoscopic aspect of the mucosa (Keshavarz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies with case finding approach that are done in these patients. The frequency of CD is reported from 1.4% [ 17 ] to 7% [ 18 ] in people with dyspeptic complaints and from 0.4% to 11.4% in patients with IBS [ 19 21 ]. A meta-analysis showed that biopsy-confirmed CD is 4-fold more prevalent in IBS patients than the general population (Pooled odds ratio = 4.34, CI 95% = 1.78–10.6) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%